Ecosistema empresarial (Estudios) - Lozano, Melquicedec (2017)
Abstract Business ecosystems have become stronger in recent years due to the strengths they have in favor of the development of the entrepreneurial spirit and the creation of new companies; however, the literature on business ecosystems is still scarce. This research starts from the design of an enterprise ecosystem to determine the components that should conform it, how they should be related to interact in an organized manner and what the actions to be executed should be.